Pengaruh Kesejahteraan Karyawan dan Hubungan Interpersonal terhadap Produktivitas Kerja dengan Kepuasan Kerja sebagai Variabel Intervening di PTP Inti 4 Kinali Pasaman Barat - Hayatul Hafifa; M. Afuan; Engla Desnim Silvia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to examine the influence of employee well-being and interpersonal relationships on work productivity with job satisfaction as an intervening variable using primary data obtained by distributing questionnaires to 73 employees, namely at PTP Inti 4 Kinali Pasaman Barat. The results of this research show that (1) there is a positive and significant influence between employee well-being and job satisfaction. (2) there is a positive and significant influence between interpersonal relationships on job satisfaction (3) there is a positive and significant influence between employee well-being on work productivity. (4) there is a positive and insignificant influence between interpersonal relationships and work productivity. (5) there is a positive and insignificant influence between job satisfaction and work productivity. (6) there is a positive and insignificant influence between employee welfare on work productivity through job satisfaction. There is a positive and insignificant influence between interpersonal relationships and job satisfaction.